Investigation on the application of ZnO nanostructures to improve the optical performance of white light-emitting diodes - My Hanh Nguyen Thi; Phung Ton That; Hoang Van Ngoc (Universitas Ahmad Dahlan, 2021)
Though combining blue LED chips with yellow phosphor has been the most common method in white light-emitting diode (WLED) production, the attained angular correlated color temperature (CCT) uniformity is still poor. Thus, this article proposes to add ZnO nanostructures to WLED packages to promote the color uniformity of the WLEDs. The outcomes of the research demonstrate that utilizing ZnO at different amount can affect the scattering energy and the CCT deviations in WLEDs packages in different extents. Particularly, adding the node-like (N-ZnO), sheet-like (S-ZnO), and rod-like (R-ZnO) leads to the corresponding decreases of CCT deviations from 3455.49 K to 96.30 K, 40.03 K, and 60.09 K, respectively. Meanwhile, with 0.25% N-ZnO, 0.75% S-ZnO, and 0.25 % R-ZnO, WLED devices can achieve both better CCT homogeneity and lower reduction in luminous flux. The results of this article can be a valuable document for the manufacturer to use as reference in improving their WLED products.